2011
DOI: 10.1108/17582951111136568
|View full text |Cite
|
Sign up to set email alerts
|

Social media use in sports and entertainment venues

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 6 publications
0
24
0
2
Order By: Relevance
“…Prior research in marketing has generally identified more positive effects of social media presence than absence. Rothschild (2011) looked at how social media is used, managed, and perceived by sports and entertainment venue managers, and found that many (57%) have a defined social media strategy, and experience higher revenues than those that do not. A recent study by Medallia found that hotel properties that actively engage with social media reviews grow occupancy at double the rate of properties that don"t (Hertzfeld, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Prior research in marketing has generally identified more positive effects of social media presence than absence. Rothschild (2011) looked at how social media is used, managed, and perceived by sports and entertainment venue managers, and found that many (57%) have a defined social media strategy, and experience higher revenues than those that do not. A recent study by Medallia found that hotel properties that actively engage with social media reviews grow occupancy at double the rate of properties that don"t (Hertzfeld, 2015).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…However, there was a lack of clarity in terms of which platform was most relevant to participants, as well as resource challenges in managing these tools. Events with a defined social media strategy report higher revenue (Rothschild, 2011). To this end, staffing needs must be addressed to ensure that social media platforms are optimised as tools to collect participant attitudes and opinions.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…The SM as an advertising tool is considered as the most prevalent way of communication (Rothschild, 2011). Concentrating on the SMTs are so effective way for the professional football clubs and players to reach a high-quality connection with extra monitoring during the announcement of sport news and swelling their survival running (Sanderson and Kassing, 2011).…”
Section: The Key Social Media Tools In the Football Sport Clubsmentioning
confidence: 99%
“…Results presented that the social media is a powerful way for developing the marketing strategy of the football sport clubs in Northern Iraq and they can make success by embracing these media tools, because practicing the traditional media needs financial resources in Northern Iraq, when the financial situation of many football clubs in Northern Iraq is not good, hence the football clubs can implement their objectives via the social media as a marketing strategy. White et al (2017), explain that social media marketing is a process which has engaged in leveraging social interactivity between consumers in free social media scenes with a quick-paced stream of information, furthermore the social media tools have granted a new framework of the communication method, it is recognized as a vital part of interactive marketing communications, as well as consumers practice the social media stations to interact with each other or companies, therefore many marketers establish the social media into their marketing strategy, similarly Rothschild, (2011) growth in the marketing strategy of the football clubs because they are more concentrated on social media, particularly Facebook to engage the fans for a better advertising method and also more practical communication approaches.…”
Section: Conclusion Implications and Limitationsmentioning
confidence: 99%